Anomalous Pulmonary Vein Drainage Is Not a Contraindication for VATS Lobectomy - Shapiro, M.; Bittermann, C.; Flores, R. M. (The Thoracic and Cardiovascular Surgeon, 2014)
This is a case report on a 26-year-old woman with metastatic mandibular osteosarcoma to the lung. A video-assisted thorascopic surgery (VATS) completion left upper lobe lobectomy was attempted, but was converted to a thoracotomy when anomalous pulmonary vein drainage (APVD) was identified. There were no other anomalies found and the lobectomy was completed as planned. To our knowledge, this is the first reported case of an attempted VATS lobectomy for patients with APVD. This case demonstrates that APVD tends not to be associated with any other anatomic abnormalities in the lung and should not be a contraindication for VATS lobectomy.
Keywords: metastasectomy; thoracoscopy; pulmonary veins